Genetic Diversity of Klebsiella spp. Isolated from Tempe based on Enterobacterial Repetitive Intergenic Consensus-Polymerase Chain Reaction (ERIC-PCR) - TATI BARUS; IVAN HANJAYA; JOANITA SADELI; BIBIANA W LAY; ADI YULANDI; ANTONIUS SUWANTO (Bogor Agricultural University, Indonesia, 2013)
Tempe is an Indonesian fermented food prepared by fermenting dehulled cooked soybeans with Rhizopus oligosporus. Many types of bacteria are also involved during tempe fermentation, and one of these is Klebsiella spp. Some isolates of K. pneumoniae produces vitamin B12 in tempe but it has also been classified as an opportunistic pathogen. For this reason Klebsiella spp. in tempe is important to be studied. The aim of this study was to investigate the genetic diversity of Klebsiella spp. from tempe employing ERIC-PCR method. Sixty-one isolates of Klebsiella have been isolated from sixteen tempe producers in Bogor, Jakarta, Malang, Tengerang, Bandung and Cianjur. 63F and 1387R primers were used to amplify 16S rDNA sequences, and 1R and 1F primers were used for ERIC analysis. The results of this research showed that sixty-one strains of Klebsiella were clustered into 17 groups. Based on ERIC-PCR analysis, isolates of Klebsiella could be grouped into different profiles which some of these groups consisted of isolates with identical ERIC-PCR profiles. Several identical ERIC-PCR profiles were found in tempe from the same producer. There was no correlation observed between genetic similarity among isolates with the origin of tempe.